STRATEGI PENGELOLAAN ORGANISASI SENI Studi Kasus: Young Musical Fantasy - Desy Lia Arlistya (Pascasarjana Institut Seni Indonesia Padang Panjang, 2018)
ABSTRACT This research aims at knowing the internal and external factors of the condition of art organization that becomes the medium of musical learning in Young Musical Fantasy in order to become the basis of arranging the alternative of management strategy in this organization. The method used in this research was the descriptive qualitative method with the approach of the case study. The analysis unit of this research was the staff management of Young Musical Fantasy, and the technique of data collection in this research was by doing the interview with interviewees believed to be able to give accurate information. Researcher also conducted the field study. Data were processed by using table IFE & EFE Matrix, SWOT Matrix, and IE Matrix obtained through the analysis of strength, weakness, opportunity, and threat. The result of this research shows that by looking at the position of Young Musical Fantasy through SWOT analysis, it shows Hold and Maintain, and generic strategy that must be applied by Young Musical Fantasy is the stability strategy in which the community maintains its community size and its existing products for its consumers.Keywords: external and internal analysis, SWOT analysis, generic strategy, and strategy variation ABSTRAKPenelitian ini bertujuan untuk mengetahui faktor internal dan eksternal kondisi dari organisasi seni yang menjadi wadah pembelajaran musik pada Young Music Fantasy sebagai dasar dalam menyusun alternatif strategi pengelolaan pada organisasi ini. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan pendekatan studi kasus.Unit analisis penelitian ini adalah staff management dari Young Musical Fantasy dan teknik pengumpulan data dalam penelitian ini, yaitu dengan melakukan wawancara kepada narasumber yang dipercaya dapat memberikan informasi yang akurat.Peneliti juga melakukan penelitian lapangan. Data diproses dengan menggunakan tabel IFE & EFE Matrix, SWOT Matrix dan IE Matrix yang diperoleh melalui analisis kekuatan, kelemanan, peluang dan ancaman.Hasil dari penelitian ini menunjukkan bahwa dengan melihat posisi Young Musical Fantasy melalui analisis SWOT menunjukkan Hold and Maintain(pertahankan dan pelihara), strategi generik yang mestinya dijalankan Young Musical Fantasy adalah strategi stabilitas, dimana komunitas mempertahankan ukuran komunitasnya dan mempertahankan produk yang telah ada kepada konsumennya.